2015
DOI: 10.21273/hortsci.50.4.522
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Acclimation of Impatiens, Salvia, Petunia, and Tomato Seedlings to Blue and Red Light

Abstract: Plant growth is plastic and adaptive to the light environment; characteristics such as extension growth, architecture, and leaf morphology change, depending on the light spectrum. Although blue (B; 400–500 nm) and red (R; 600–700 nm) light are generally considered the most efficient wavelengths for eliciting photosynthesis, both are often required for relatively normal growth. Our objective was to quantify how the B:R influenced plant seedling growth and morphology and understand how plants acclimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
35
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 46 publications
5
35
2
1
Order By: Relevance
“…For example, Hern andez and Kubota (2016) found that as the percentage of blue light provided by red:blue LEDs increased (up to 75%) at a light intensity of 100 mmol · m -2 · s -1 , seedlings of cucumber (Cucumis sativus) 'Cumlaude' displayed shorter hypocotyls and a smaller leaf area. Similar responses have been observed with bedding plant seedlings produced under sole-source LED lighting; seedlings grown under sufficient intensities of blue light ($10 mmol · m -2 · s -1 ) were often more compact and of higher quality Lopez, 2014, 2015;Wollaeger and Runkle, 2015). Although many such responses have been observed under solesource lighting environments, the benefit of spectrum manipulation for SL in the greenhouse remains uncertain.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…For example, Hern andez and Kubota (2016) found that as the percentage of blue light provided by red:blue LEDs increased (up to 75%) at a light intensity of 100 mmol · m -2 · s -1 , seedlings of cucumber (Cucumis sativus) 'Cumlaude' displayed shorter hypocotyls and a smaller leaf area. Similar responses have been observed with bedding plant seedlings produced under sole-source LED lighting; seedlings grown under sufficient intensities of blue light ($10 mmol · m -2 · s -1 ) were often more compact and of higher quality Lopez, 2014, 2015;Wollaeger and Runkle, 2015). Although many such responses have been observed under solesource lighting environments, the benefit of spectrum manipulation for SL in the greenhouse remains uncertain.…”
supporting
confidence: 53%
“…One means by which excessive extension growth may be suppressed is through manipulation of the light spectrum. Specifically, blue light has commonly been linked to growth inhibition of bedding plant seedlings (Randall and Lopez, 2014;Wollaeger and Runkle, 2015). For example, Randall and Lopez (2014) observed shorter stem lengths for snapdragon (Antirrhinum majus) 'Rocket Pink', vinca (Catharanthus roseus) 'Titan Punch', celosia (Celosia argentea var.…”
Section: Discussionmentioning
confidence: 99%
“…Current research demonstrates that light quality can impact plant growth and biomass accumulation of specialty crops in controlled environments . In a recent study, shoot FM (g per plant) in 28‐day‐old Chinese cabbage ( Brassica chinensis ) was significantly higher under high pressure sodium (HPS) lighting compared to a 7: 1 ratio of red (650 nm) and blue (470 nm) LED light at an equal intensity of 391 ± 24 µmol m −2 s −1 .…”
Section: Resultsmentioning
confidence: 99%
“…'Ellen';Kuril cik et al, 2008), and yarrow (Achillea millefolium L.; Alvarenga et al, 2015). Previous literature indicates that plants generally use B light less efficiently for photosynthesis (Wollaeger and Runkle, 2015), thus limiting the production of photosynthates required for biomass accumulation (Currey and Lopez, 2013). In the Wand flower leaf, shoot, and total biomass accumulation increased linearly from 2 to 10 d under SL, whereas cuttings under LED SSL did not exhibit a statistical response of biomass accumulation to light quality.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has investigated the effects of DLI and SL from high-pressure sodium (HPS) lamps and LEDs during AR development and subsequent rhizogenesis of numerous genera of vegetatively propagated annual bedding plants Hutchinson et al, 2012;Lopez and Runkle, 2008). In controlled environments, the effects of SSL provided by LEDs during seedling (plug) propagation (Randall and Lopez, 2015;Wollaeger and Runkle, 2015) and in vitro propagation (Budiarto, 2010;Gu et al, 2012;Jao et al, 2005) have been documented.…”
mentioning
confidence: 99%